Strengthening Character Education through the Implementation of Madrasah’s Culture: A Study at State Islamic Primary School 1 Bantul - Laelatul Badriah; Erlina Silfa Pratiwi; Muhammad Yusuf (Tarbawi, 2020)
The study aims to discover the habits that are entrenched in State Islamic Primary School that can influence the formation of learner character values which focused on reading culture and healthy school culture. This study used a descriptive approach and data collection techniques used interviews, observation, and documentation. Besides, the questionnaire was also used to support the data. The subjects of the study were the school principal, board of teachers, staff, and students. The qualitative descriptive analysis used in the form of data reduction (data reduction), data presentation (data display), and conclusions (conclusion drawing/verification). The results of this study showed that State Islamic Primary School 1 Bantul has a madrasah’s culture that is formed based on three main cultures, namely academic culture, social culture, and democratic culture. The culture produced the Madrasah Excellence Program. Through the program, it can build honor characters to students in the form of discipline, responsible, independent, care for the environment, and friendly as well as communicative.